Stable Au–C bonds to the substrate for fullerene-based nanostructures - Chutora, Taras; Redondo, Jesús; de la Torre, Bruno; Švec, Martin; Jelínek, Pavel; Vázquez, Héctor (Beilstein Journal of Nanotechnology, 2017)
We report on the formation of fullerene-derived nanostructures on Au(111) at room temperature and under UHV conditions. After low-energy ion sputtering of fullerene films deposited on Au(111), bright spots appear at the herringbone corner sites when measured using a scanning tunneling microscope. These features are stable at room temperature against diffusion on the surface. We carry out DFT calculations of fullerene molecules having one missing carbon atom to simulate the vacancies in the molecules resulting from the sputtering process. These modified fullerenes have an adsorption energy on the Au(111) surface that is 1.6 eV higher than that of C60 molecules. This increased binding energy arises from the saturation by the Au surface of the bonds around the molecular vacancy defect. We therefore interpret the observed features as adsorbed fullerene-derived molecules with C vacancies. This provides a pathway for the formation of fullerene-based nanostructures on Au at room temperature.
Keywords: Au–C bonds; density functional theory (DFT); fullerenes; scanning tunneling microscopy (STM); sputtering